UAV-Based Airport Lights Inspection Without GNSS Positioning Support - Wiesław Pamuła; Teresa Pamuła; Tomasz Stenzel; Maciej Sajkowski; Adam Rytter; Daria Żuchowska (Remote Sensing)
The inspection of PAPI (precision approach path indicator), ALS (approach light system), and runway lights is the basis of maintenance actions that safeguard the safety of airport operations. These actions consist of measurements requiring the accurate positioning of reference viewing points. Commonly, GNSS-based methods are employed and augmentation procedures are applied to improve the positioning precision. Augmentation involves the use of additional sources of information such as reference stations and complicates the process of position calculations. An image processing-based method is proposed for triangulating the positions of reference viewing points during inspections of airfield lights using a UAV. The Structure-from-Motion (SfM) photogrammetric range imaging technique and airport geodesic data are the basis of the method. The measurement of PAPI transition angles is presented as an application example. The results are compared to GNSS-based measurements and prove the viability of the method.